2022
DOI: 10.1002/acp.3908
|View full text |Cite
|
Sign up to set email alerts
|

Remember to stay positive: Affect and prospective memory in everyday life

Abstract: The present study aimed to investigate the affect-cognition interplay in young and older adults by studying prospective memory (PM), the realisation of delayed intentions. While most previous studies on the topic were conducted in the laboratory, we examined the influence of naturally occurring affect on PM tasks carried out in participants' everyday lives. For seven consecutive days, participants were asked to rate their affective state nine times per day and send text messages either at specific times (time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Our findings are in line with the results of an ambulatory assessment study in young and older adults, which showed that more daily negative affect was associated with worse daily event-based and time-based prospective memory performance [7]. Our findings are also in line with an ambulatory assessment study on working memory, which showed higher high-arousal negative affect (i.e., nervousness) to be associated with lower working memory performance at the same moment in middle-and older aged adults [21].…”
Section: Daily Affect-prospective Memory Associationssupporting
confidence: 91%
See 4 more Smart Citations
“…Our findings are in line with the results of an ambulatory assessment study in young and older adults, which showed that more daily negative affect was associated with worse daily event-based and time-based prospective memory performance [7]. Our findings are also in line with an ambulatory assessment study on working memory, which showed higher high-arousal negative affect (i.e., nervousness) to be associated with lower working memory performance at the same moment in middle-and older aged adults [21].…”
Section: Daily Affect-prospective Memory Associationssupporting
confidence: 91%
“…This study was an initial attempt to examine affect in daily life, but its focus on a sporting context constrains its generalizability. Recently, a 7-day ambulatory assessment study invited young and older adults, nine times per day, to report their affect and complete an event-based prospective memory task (i.e., replying to text messages that had a word in upper case) and a time-based prospective memory task (i.e., sending text messages at predefined times) [7]. Results indicated that naturally occurring positive (vs. negative) affect was associated with better daily performance in both event-based and time-based prospective memory tasks.…”
Section: Affect-prospective Memory Associationsmentioning
confidence: 99%
See 3 more Smart Citations